KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI DALAM SISTEM KETATANEGARAAN INDONESIA - Mahesa Rannie (Lex Librum : Jurnal Ilmu Hukum, 2021)
Abstrak Kedudukan Komisi Pemberantasan Korupsi (KPK) dalam sistem ketatanegaraan Indonesia memang seringkali diperdebatkan, hal ini terbukti dengan Putusan-Putusan MK yang berubah-ubah. Mahkamah Konstitusi dalam putusannya pernah beberapa kali memutuskan berbeda tentang kedudukan KPK ini dalam sistem ketatanegaraan Indonesia. Mahkamah Konstitusi pernah memutuskan KPK merupakan lembaga negara independen di luar ranah kekuasaan eksekutif, legislatif, dan yudikatif. Pernah pula memutuskan bahwa KPK merupakan eksekutif dilihat dari kewenangannya. Putusan-putusan MK ini tentu saja membawa pengaruh terhadap undang-undang KPK. Revisi undang-undang KPK terbaru, yaitu Undang-Undang Nomor 19 Tahun 2019 menyatakan KPK masuk dalam ranah kekuasaan eksekutif sehingga dengan demikian KPK dapat menjadi objek hak angket Dewan Perwakilan Rakyat (DPR). Hal demikian tentu saja menambah panjang perdebatan di kalangan ahli hukum dengan argumentasinya masing-masing. Dari argumentasi-argumentasi tersebut penulis menganggap KPK adalah lembaga negara independen di luar struktur organ negara yang utama. Hal ini sejalan dengan theory the new separation of power sebagai konsekuensi dari teori negara kesejahteraan (welfare state) di era abad modern ini. Sebagai lembaga negara independen yang kedudukannya tidak sekuat lembaga negara utama dalam ranah kekuasaan eksekutif, legislatif, dan yudikatif tentu saja KPK bisa dibubarkan jika lembaga yang selama ini sebetulnya mempunyai wewenang kuat untuk melaksanakan penegakan hukum dalam rangka pemberantasan tindak pidana korupsi (Kepolisian dan Kejaksaan) mampu berbenah diri. Selama belum mampu berbenah maka wewenang tersebut bisa dilaksanakan oleh KPK yang keberadaannya sampai saat ini masih tetap diperlukan dalam rangka pemberantasan tindak pidana korupsi di Indonesia. Kata kunci: Kedudukan KPK, Sistem Ketatanegaraan, Indonesia Abstract The position of the Corruption Eradication Commission (KPK) in the constitutional system of Indonesia is often debated. This is evidenced by the inconsistent decisions of the Constitutional Court. The Constitutional Court has ever made different decisions several times regarding the position of the Corruption Eradication Commission (KPK) in the constitutional system of Indonesia. The Constitutional Court once decided that the Corruption Eradication Commission (KPK) was an independent state institution outside the realm of executive, legislative and judicial powers. It has also decided that the Corruption Eradication Commission (KPK) is an executive body in terms of its authority. These inconsistent decisions of the Constitutional Court, of course, have an influence on the law of the Corruption Eradication Commission (KPK). The latest revision of the law of the Corruption Eradication Commission (KPK), namely the Law Number 19 of 2019 states that the Corruption Eradication Commission (KPK) is classified to be in the realm of executive power so that the Corruption Eradication Commission (KPK) can become the object of the right to inquiry by the House of Representatives (DPR). This situation, of course, adds to the length of debate among legal experts with their respective arguments. Based on these arguments, the writer considers that the Corruption Eradication Commission (KPK) is an independent state institution outside the main state organ structure. This is in line with the theory of the new separation of power as a consequence of the theory of the welfare state in this modern era. As an independent state institution whose position is not as strong as the main state institutions in the realm of executive, legislative and judicial powers, of course, the Corruption Eradication Commission (KPK) can be dissolved if the institutions that actually have strong authority to carry out law enforcement in the context of eradicating criminal acts of corruption (Police and Prosecutors) are able to empower themselves to execute their authority. However, if those institutions have not been able to execute their authority, this authority can be exercised by the Corruption Eradication Commission (KPK), whose existence is still needed in the context of eradicating criminal acts of corruption in Indonesia.